2006
DOI: 10.1021/jp061331m
|View full text |Cite
|
Sign up to set email alerts
|

Imidazo[1,2-a]pyrazine-3,6-diones Derived from α-Amino Acids:  A Theoretical Mechanistic Study of Their Formation via Pyrolysis and Silica-Catalyzed Process

Abstract: Imidazo[1,2-a]pyrazine-3,6-diones are unusual compounds composed of three alpha-amino acid fragments. These bicyclic amidines (BCAs) form under high temperatures or with the use of strong dehydrating reagents. We gave insight into the mechanisms of BCA formation via gas-phase pyrolytic and silica-catalyzed reactions of glycine (Gly) and alpha-aminoisobutyric acid (AIB) with related diketopiperazines (DKPs), using quantum chemical calculations. The entire process requires four steps: (1) O-acylation of DKP with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…O-N Intramolecular acyl migration has found a wide use in organic chemistry [122][123][124][125][126]. Thus, this rearrangement has been applied in the synthesis of peptidomimetics: including -secretase inhibitors [127,128], prolyl endopeptidase inhibitor eurystatin A [129], HIV-protease inhibitors [130], and many others [131][132][133][134][135][136][137].…”
Section: Other Application Of O-n Intramolecular Acyl Migration Reactionmentioning
confidence: 99%
“…O-N Intramolecular acyl migration has found a wide use in organic chemistry [122][123][124][125][126]. Thus, this rearrangement has been applied in the synthesis of peptidomimetics: including -secretase inhibitors [127,128], prolyl endopeptidase inhibitor eurystatin A [129], HIV-protease inhibitors [130], and many others [131][132][133][134][135][136][137].…”
Section: Other Application Of O-n Intramolecular Acyl Migration Reactionmentioning
confidence: 99%
“…The latter fact can be directly associated with the selective detection, thermochemical stability, or simply because cycle-condensation reactions of amino acids are not able to produce enough amounts of imidazo­[1,2- a ]­pyrazines. Previous quantum chemical calculations suggested that the formation of imidazo­[1,2- a ]­pyrazines can proceed overcoming a high reaction barrier of about 49 kcal mol –1 and only supported by a silica-catalyzed process. This has opened up an area of great dubiety about the formation and the spectroscopic properties of imidazo­[1,2- a ]­pyrazines, which deserves more definitive answers and novel approaches for experimental identification.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, time-dependent DFT (TD-DFT) calculations were carried out to access the orbital contributions to each of the transitions observed in the absorption spectrum, and molecular excitation energies were obtained for both isolated molecule and metallic cluster-organic compounds. Arising from sublimation of α-amino-acids (e.g., glycine), bi and tricyclic imidazo­[1,2- a ]­pyrazines prepared require the formation of a first intermediate . The current series of molecules studied correspond to glycine (Gly, 1 ), piperazine-2,5-dione (DKP, 2 ), hexahydroimidazo­[1,2- a ]­pyrazine-3,6-dione (BCA, 3 ), and hexahydroimidazo­[1,2- a ]­imidazo­[1,2- d ]­pyrazine-3,8-dione (TCA, 4 ), which all are depicted in Scheme .…”
Section: Introductionmentioning
confidence: 99%
“…This reaction probably proceeds through the corresponding cyclic dipeptides. [14,17] In the course of our studies on a-amino acids in different binding states, [15,[18][19][20] we have noticedt hat information about the solid thermolysis products that form from neat bulk glycine is scarce. This is surprising not only because glycinei st he simplest amino acid but also because it is considered highly relevant in prebiotic chemistry studies.…”
Section: Introductionmentioning
confidence: 99%